(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To compare the functional outcome of paediatric supracondylar fractures of the humerus treated with closed reduction and percutaneous(CRP) K wire fixation versus open reduction(OR) and K wire fixation. Methods: The design of our study was retrospective Cohort and was conducted in Department of Orthopaedics Civil Hospital Karachi. The medical record of all the children who were operated in the time period of 8th March 2019 to 07th September 2020 for type III distal humerus fractures were reviewed. All the children fulfilling the inclusion criteria were called for follow up. Patients were divided into group A(CRP crossed K wire fixation) and group B(OR crossed K wire fixation through posterior midline incision with triceps sparing approach). Functional outcome in both groups was evaluated with Flynn’s criteria and graded as Excellent, Good, Fair(satisfactory) and Poor(unsatisfactory).The results of both group A and B were compared and statistical significance documented by calculating P value with Chi-Square test(P <0.05 significant). Results: The total number of children were 60 and divided equally into Group A(n=30) and Group B(n=30).The mean age of group A was 6±1.1 years and group B 6.9 ± 3.83 years. Male children were 21(70%) in Group A and 18(60%) in group B while female children were 9(30%) and 12(40%) in Group A and Group B respectively.in Group A children results were excellent in 21(70%) and good in 9(30% ) children. In group B excellent results were noted in 9(30% ),good in 08(26.6%), fair in 6(20%) and poor in 7(23.3% )children. The difference among the excellent, fair and poor outcome of the two groups was found significant( P Value < 0.05) Conclusion: CRP K wire fixation of supracondylar fractures of the humerus was better than OR K wire fixation because it yielded excellent and good outcome in most patients